Revisiting the Spirit of Religious Nationalism in the Era of Pluralism and Globalization: Reading the Text of NDP of HMI - Al Makin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
This article is a reflection of the text of NDP (Nilai Dasar Perjuangan/Basic Principles of Struggle) text held by HMI (Himpunan Mahasiswa Islam/Muslim Student Association) as a basis of their activism struggle in Indonesia. The text consists of eight sections covering many aspects, such as theology, anthropology, sociology, and epistemology. By critical thinking, the NDP text of HMI should be transformed continuously toward an era of global diversity and plurality. In Indonesian context, there has been a fundamental change along with the democratization that brings out an openness and multi-party political system. This is important regarding that the NDP of HMI has been drafted in 1960 and 1970 when Nurcholis Madjid era faced the context of socio-political thought. The study found that the NDP of HMI is required to be changed in the context of new world order. It is not a sacred text, so the change is a necessity.